2017
DOI: 10.1161/jaha.117.006264
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Acute Obstructive Sleep Apnea: Autonomic Nervous Mechanism and Modulation

Abstract: BackgroundThe mechanisms of atrial fibrillation (AF) induced by obstructive sleep apnea (OSA) are not completely understood. This study investigated the roles of the intrinsic and extrinsic cardiac autonomic nervous system in OSA‐induced AF and provided noninvasive autonomic nervous modulation for the suppression of OSA‐induced AF by using low‐level transcutaneous electrical stimulation (LL‐TS) of the auricular branch of the vagus nerve at the tragus.Methods and ResultsEighteen dogs received tracheostomy under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 35 publications
0
26
1
Order By: Relevance
“…Many studies have been performed in regard to the mechanism and therapeutic strategies of AF. Multiple factors, including advancing age, male sex, obesity, heart failure, obstructive sleep apnea, anxiety, systemic arterial hypertension, and biomarkers such as N-terminal pro-Btype natriuretic peptide (NT-proBNP), have been identified as factors correlated with AF development [12][13][14][15]. Our study showed that the level of plasma Neu5Ac was significantly higher in the AF group than in the control group, indicating that Neu5Ac was significantly correlated with AF.…”
Section: Discussionmentioning
confidence: 63%
“…Many studies have been performed in regard to the mechanism and therapeutic strategies of AF. Multiple factors, including advancing age, male sex, obesity, heart failure, obstructive sleep apnea, anxiety, systemic arterial hypertension, and biomarkers such as N-terminal pro-Btype natriuretic peptide (NT-proBNP), have been identified as factors correlated with AF development [12][13][14][15]. Our study showed that the level of plasma Neu5Ac was significantly higher in the AF group than in the control group, indicating that Neu5Ac was significantly correlated with AF.…”
Section: Discussionmentioning
confidence: 63%
“…At present, the exact mechanism underlying the initiation, maintenance and recurrence of atrial fibrillation is unclear. Although previous studies have demonstrated that remodeling and regeneration of the sympathetic nervous system are associated with the occurrence and maintenance of atrial fibrillation (23)(24)(25), there is a lack of detailed information. In order to better understand the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that low-level vago-sympathetic trunk stimulation (LLVS) at voltages that do not slow the sinus rate or AV conduction, could decrease AF inducibility and AF duration, and prolonged ERP induced by acute OSA on a rabbit model ( Gao et al, 2015 ), but no changes have yet been manifested in the structural remodeling of the left atrium (LA). Yu et al (2017) demonstrated that noninvasive low-level transcutaneous electrical stimulation could prevent the incidence of AF in a 1-h OSA dog model. They also recorded neural activity from the superior left ganglionated plexus (SLGP), the left stellate ganglion (LSG), and the left renal sympathetic nerve (RSN), as well as changes in fast neuron markers in SLGP and LSG, but the nerve distribution in LA has not yet been investigated.…”
Section: Introductionmentioning
confidence: 96%